Analysis of students’ difficulties in speaking skills in studying English - Tristasari, Safirah; Yuliati (Universitas Negeri Semarang, 2025)
The aim of this study is to examine the challenges that students have when studying English as a Foreign Language in order to improve their speaking abilities. Speaking is an essential part of language proficiency, but many students struggle with a variety of issues that make it difficult for them to speak clearly. This study used an integrative literature review method and to collect data using previous studies. The results show that during speaking practices, students most commonly struggle with pronunciation, vocabulary constraints, anxiousness, and lack of confidence. Their challenges are also significantly heightened by a lack of practice chance and fear of making mistakes. The study also highlights outside variables as impediments to speaking ability improvement, such as insufficient classroom engagement and little exposure to native speakers. In light of these findings, the study recommends that teachers use more engaging and encouraging teaching strategies, such as role-plays, group discussions, and pronunciation exercises, to improve their students’ speaking skills. Additionally, fostering an environment that is supportive and upbeat might help students feel less anxious and more confident. For educators and curriculum developers, improving students’ English-speaking skills is essential to help them succeed in global communication.